2016
DOI: 10.1038/srep31176
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Highly Active Cephalopod S-crystallin Mutant: New Molecular Evidence for Evolution from an Active Enzyme into Lens-Refractive Protein

Abstract: Crystallins are found widely in animal lenses and have important functions due to their refractive properties. In the coleoid cephalopods, a lens with a graded refractive index provides good vision and is required for survival. Cephalopod S-crystallin is thought to have evolved from glutathione S-transferase (GST) with various homologs differentially expressed in the lens. However, there is no direct structural information that helps to delineate the mechanisms by which S-crystallin could have evolved. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Eye crystallins represent a different case in which housekeeping genes were co-opted to promote transparency and optical clarity of the lens. Remarkably, only four point mutations were required to restore the glutathione S-transferase activity of cephalopod S-crystallin, which was exapted from an ancestral GST ( 94 ). Minute numbers of base changes are also effective in reassignment of non-coding RNA functions.…”
Section: Discussionmentioning
confidence: 99%
“…Eye crystallins represent a different case in which housekeeping genes were co-opted to promote transparency and optical clarity of the lens. Remarkably, only four point mutations were required to restore the glutathione S-transferase activity of cephalopod S-crystallin, which was exapted from an ancestral GST ( 94 ). Minute numbers of base changes are also effective in reassignment of non-coding RNA functions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as pointed out by Tomarev et al ( 1991 ) the use of detoxification stress proteins like GST and aldehyde dehydrogenase as cephalopod crystallins, is indicative of a common strategy for recruitment of enzyme-crystallins during the convergent evolution of vertebrate and invertebrate lenses. A recent study on O. vulgaris has revealed that the loss of GST enzyme activity in lens tissue is linked to the enhanced protein stability of S-crystallin via glutathione binding (Tan et al, 2016 ). In the light of these data, and although protein identification in our study was not carried out at the cellular location level, it is tempting to suggest that the decrease of GST might also be indicative of possible alterations in the lens structure of starved paralarvae.…”
Section: Discussionmentioning
confidence: 99%
“…It is also the predominant isoform of crystallin found in the bioluminescent light organ of the Hawaiian bobtail squid Euprymna scolopes 25 . Although the S- and Ω-isoforms are compositionally dissimilar, they share (i) high-refractive indices, (ii) optical transparency, and (iii) solubility in water, suggesting key functional roles in both the eyes and skin of the animals 21,24,26 . The structural protein reflectin is cephalopod-specific and aggregates into nanoparticles or self-assembles into ribbons 2729 , contributing to its ability to scatter and reflect light that produces colorful iridescence or diffuse whiteness 30,31 .…”
Section: Introductionmentioning
confidence: 99%